Unbecoming citizens culture, nationhood, and the flight of refugees from Bhutan - Hutt, Michael (Michael J.) (New Delhi ; Oxford : Oxford University Press, 2005)
During the early 1990s, approximately 95,000 people arrived in eastern Nepal. They claimed to have come from Bhutan, and they alleged they had been forced out by the Bhutanese government. This text explains who these people were and why they left Bhutan.
Originally published: 2003.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Refugees -- Bhutan; Refugees -- Nepal; Nepalese -- Bhutan -- History; Ethnicity -- Bhutan; Bhutan -- Politics and government